STRATEGI PEMBERDAYAAN PETERNAK DALAM USAHA KONSERVASI SAPI JAWI PANDAAN DI KECAMATAN PRIGEN KABUPATEN PASURUAN - N. Supartini; H. Darmawan (Universitas Tribhuwana Tunggadewi, 2012)
Prigen district is one of the development zone of husbandary Jawi Pandaan Cow is East Java local breed one of the local breed which have similar characteristic with Bali cow. Aim of this research is to identify factors of empowered strategies of Jawi Pandaan cow’s farmer at Prigen district in order to conservation. This research used simple random sampling method. Materials research were 88 farmer who have 381 cows. Data analized using descriptive analysis. Conclusion of this research showed that empowered strategies of Jawi Pandaan cow’s farmer at Prigen district in order to conservation need regulation which protect the purebred, and empowered strategies by people centered, participatory, empowering and sustainable priciples. Need other programs, such as elite bull program, market orientation for production system, integrated and continously famer welfare development program